The girl who saw Heaven : a fateful tornado and a journey of faith - Reburn, Lisa; Tresniowski, Alex (Simon & Schuster, 2023)
"Shares the story of Ari Hallmark, who is now a high school senior, and what happened to her during the tornado that claimed the lives of her parents, delivering a powerful message to the world: you will see your loved ones again"--